Transfer hydrogenation from glycerol over a Ni-Co/CeO2 catalyst: A highly efficient and sustainable route to produce lactic acid - Tang, Zhenchen; Cao, Huatang; Tao, Yehan; Heeres, Hero J.; Pescarmona, Paolo P. (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Efficient conversion of glycerol to lactate with concomitant transfer to various H2 acceptors.•A bimetallic NiCo/CeO2 catalyst showed much higher activity than the monometallic counterparts.•The NiCo/CeO2 catalyst achieved very high yield of lactic acid salt (93%) at 97% glycerol conversion.•The NiCo/CeO2 catalyst also gave high activity and selectivity in the transfer hydrogenation. Bimetallic Ni-Co catalysts supported on nanosized CeO2 were prepared and investigated as heterogeneous catalysts for the transfer hydrogenation between glycerol and various H2 acceptors (levulinic acid, benzene, nitrobenzene, 1-decene, cyclohexene) to selectively produce lactic acid (salt) and the target hydrogenated compound. The bimetallic NiCo/CeO2 catalyst showed much higher activity than the monometallic Ni or Co counterparts (with equal total metal mass), thus indicating strong synergetic effects. The interaction between the metallic sites and the CeO2 support was thoroughly characterised by means of transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), energy-dispersive X-ray spectroscopy (EDX) mapping, X-ray photoelectron spectroscopy (XPS), hydrogen-temperature programmed reduction (H2-TPR) and X-ray diffraction (XRD). Combining characterisation and catalytic results proved that the Ni species are intrinsically more active than Co species, but that incorporating Co into the catalyst formulation prevented the formation of large Ni particles and led to highly dispersed metal nanoparticles on CeO2, thus leading to the observed enhanced activity for the bimetallic system. The highest yield of lactic acid (salt) achieved in this work was 93% at 97% glycerol conversion (160 °C, 6.5 h at 20 bar N2, NaOH: glycerol = 1.5). The NiCo/CeO2 catalyst also exhibited high activity and selectivity towards the target hydrogenated products in the transfer hydrogenation reactions between glycerol and various H2 acceptors. Batch recycle experiments showed good reusability, with retention of 80% of the original activity after 5 runs.